The Influence of Nutritional Factors on Immunological Outcomes - Tourkochristou, Evanthia; Triantos, Christos; Mouzaki, Athanasia (Frontiers in Immunology, 2021)
Through food intake, humans obtain a variety of nutrients that are essential for growth, cellular function, tissue development, energy, and immune defense. A special interaction between nutrients and gut-associated lymphoid tissue occurs in the intestinal tract. Enterocytes of the intestinal barrier act as sensors for antigens from nutrients and the intestinal microbiota, which they deliver to the underlying immune system of the lamina propria, triggering an immune response. Studies investigating the mechanism of influence of nutrition on immunological outcomes have highlighted an important role of macronutrients (proteins, carbohydrates, fatty acids) and micronutrients (vitamins, minerals, phytochemicals, antioxidants, probiotics) in modulating immune homeostasis. Nutrients exert their role in innate immunity and inflammation by regulating the expression of TLRs, pro- and anti-inflammatory cytokines, thus interfering with immune cell crosstalk and signaling. Chemical substrates derived from nutrient metabolism may act as cofactors or blockers of enzymatic activity, influencing molecular pathways and chemical reactions associated with microbial killing, inflammation, and oxidative stress. Immune cell function appears to be influenced by certain nutrients that form parts of the cell membrane structure and are involved in energy production and prevention of cytotoxicity. Nutrients also contribute to the initiation and regulation of adaptive immune responses by modulating B and T lymphocyte differentiation, proliferation and activation, and antibody production. The purpose of this review is to present the available data from the field of nutritional immunology to elucidate the complex and dynamic relationship between nutrients and the immune system, the delineation of which will lead to optimized nutritional regimens for disease prevention and patient care.